2020
DOI: 10.21277/st.v43i1.306
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Leadership Expression in a Learning Organization

Abstract: Straipsnyje analizuojamos lyderystės raiškos besimokančioje organizacijoje galimybės, nagrinėjama besimokančios organizacijos apibrėžtis ir bruožai, analizuojama lyderystės samprata bei pateikiami lyderystės tipai. Remiantis atlikta mokslinės literatūros lyderystės ir besimokančios organizacijos klausimais analize, identifikuotos lyderystės raiškos besimokančioje organizacijoje galimybės bei sudarytas šių galimybių nustatymo modelis. Straipsnio tikslas yra, nustačius lyderystės raiškos besimokančioje organizac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Furthermore, LO enhances the adaptability level of employees, increasing their skills, expertise, and job satisfaction which encourages them to demonstrate IWBs (Soh, Ali, 2021). It has also been observed that LO, by utilizing the strategies of a learning culture, supporting brilliance, open communication, encouragement of knowledge sharing and experience to do reforms in their organizational policies, procedures, and practices, which encourage employees to engage themselves for higher performance and IWBs (Hidayat, Patras, 2022;Skunčikienė et al, 2009). Using the latest technologies, LO encourages the employees for the generation, execution, and implementation of novel ideas with learning (Li et al, 2022;Mustika et al, 2020).…”
Section: Learning Organizations and Innovative Work Behaviorsmentioning
confidence: 99%
“…Furthermore, LO enhances the adaptability level of employees, increasing their skills, expertise, and job satisfaction which encourages them to demonstrate IWBs (Soh, Ali, 2021). It has also been observed that LO, by utilizing the strategies of a learning culture, supporting brilliance, open communication, encouragement of knowledge sharing and experience to do reforms in their organizational policies, procedures, and practices, which encourage employees to engage themselves for higher performance and IWBs (Hidayat, Patras, 2022;Skunčikienė et al, 2009). Using the latest technologies, LO encourages the employees for the generation, execution, and implementation of novel ideas with learning (Li et al, 2022;Mustika et al, 2020).…”
Section: Learning Organizations and Innovative Work Behaviorsmentioning
confidence: 99%
“…Analyzing the meaning of learning and its impact on both the organization and the individual, its professional and personal development, it is emphasized that learning is a way of survival, capacity building, enabling it to change, i. y. to cope with changes and take advantage of new opportunities (Garbenis and Palujanskiene, 2021;Šneiderienė et al, 2020).…”
Section: Theoretical Aspects Of a School Learning Organization In A P...mentioning
confidence: 99%
“…Inevitably, educational institutions face the need for competencies in the formulation and implementation of competition policy, the meaning of learning and skills to influence the organization as new opportunities, which in itself requires knowledge based on innovative approaches (Sabaitytė, 2017;Šneiderienė et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Así pues, la teoría del liderazgo es muy amplia y variada, pero en el contexto de una organización que aprende, los tipos de liderazgo transaccional y transformacional, empoderador, colectivo y positivo son de gran importancia. (Šneiderienė, Vaitiekus y Vaitiekienė, 2020).…”
Section: Marco Teóricounclassified